Persepsi Perawat tentang Supervisi Klinis Pelaksanaan Edukasi Pasien dan Keluarga - Yetty Mariani Tambun; Setiawan Setiawan; Roymond H. Simamora (Jurnal Keperawatan Silampari, 2020)
The purpose of this study was to explore nurses' perceptions about clinical supervision in the implementation of patient and family education in Universitas Sumatera Utara. This type of research is a qualitative research with a phenomenological design. The results of this study brought out five main themes, namely (1) the purpose of supervision in the implementation of patient and family education, (2) methods of carrying out supervision, (3) the barriers that had been facing during the implementation supervision, (4) the future expectations related to the implementation of supervision and (5) the benefits of supervision implementation. Conclusions, nurses' perceptions about clinical supervision in the implementation patient and family education are important to do, even though the implementation still not optimum. Keywords: Education, Hospital, Clinical Supervision